Patterned human microvascular grafts enable rapid vascularization and increase perfusion in infarcted rat hearts - Meredith A. Redd (Nature Portfolio, 2019)
Heart grafts need good vascularization to survive. Here, the authors engineer perfusable constructs of human embryonic stem cell-derived endothelial cells seeded in collagen matrix in patterned microchannels that form anastomosed vessels in vitro and have increased coronary vascular perfusion on transplantation in rats.